2004
DOI: 10.1021/bi048692h
|View full text |Cite
|
Sign up to set email alerts
|

Isotope and Elemental Effects Indicate a Rate-Limiting Methyl Transfer as the Initial Step in the Reaction Catalyzed by Escherichia coli Cyclopropane Fatty Acid Synthase

Abstract: Cyclopropane fatty acid (CFA) synthases catalyze the formation of cyclopropane rings on unsaturated fatty acids (UFAs) that are natural components of membrane phospholipids. The methylene carbon of the cyclopropane ring derives from the activated methyl group of S-adenosyl-L-methionine (AdoMet), affording S-adenosyl-L-homocysteine (AdoHcys) and a proton as the remaining products. This reaction is unique among AdoMet-dependent enzymes, because the olefin of the UFA substrate is isolated and unactivated toward n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 62 publications
3
64
0
2
Order By: Relevance
“…Along the reaction path, the stiffness of the methyl group is further enhanced from SET8-bound SAM to the TS as reflected by a larger inverse CD3 k of 0.90. Several previous studies have reported inverse CD 3 KIEs for SAM-dependent methyltransferases and proposed that the S-N motions tighten the vibrational modes of the sulfonium-methyl moiety at the S N 2 TS (18,55,56). Our KIE measurements together with QM modeling suggest that SET8-catalyzed methylation adopts an early, asymmetrical S N 2 mechanism with more axial compression between the methyl donor and acceptor at the TS relative to the unbound and SET8-bound ground states of SAM (Fig.…”
Section: Computational Modeling Of Transition State Of Set8-catalyzedsupporting
confidence: 58%
“…Along the reaction path, the stiffness of the methyl group is further enhanced from SET8-bound SAM to the TS as reflected by a larger inverse CD3 k of 0.90. Several previous studies have reported inverse CD 3 KIEs for SAM-dependent methyltransferases and proposed that the S-N motions tighten the vibrational modes of the sulfonium-methyl moiety at the S N 2 TS (18,55,56). Our KIE measurements together with QM modeling suggest that SET8-catalyzed methylation adopts an early, asymmetrical S N 2 mechanism with more axial compression between the methyl donor and acceptor at the TS relative to the unbound and SET8-bound ground states of SAM (Fig.…”
Section: Computational Modeling Of Transition State Of Set8-catalyzedsupporting
confidence: 58%
“…3,57 S -Adenosylhomocysteine nucleosidase (SAHN) and SAM were prepared as described previously. 58,59 [8,8,8- 2 H 3 ]-Octanoyl-H protein (OHP) was synthesized using Ec LplA as described previously. 3,32 …”
Section: Methodsmentioning
confidence: 99%
“…This enhanced reactivity of AdoSeMet (33) implies that its methyl group is more reactive towards nucleophiles, which is consistent with an enhanced reactivity of trimethylselenonium hydroxide compared to trimethylsulfonium hydroxide [116]. These chemical differences between the three cofactors were used to study the enzymatic mechanism of CFA synthase acting on an isolated double bond [117]. The turnover number (TON) with AdoSeMet (33) is increased, whereas that with AdoTeMet (34) is decreased relative to AdoMet (1).…”
Section: Selenium and Tellurium Analogues Of Adometmentioning
confidence: 59%